Effects of yoga breathing exercises on pulmonary function in patients with Duchenne muscular dystrophy: an exploratory analysis, - Rodrigues, Marcos Rojo (Sociedade Brasileira de Pneumologia e Tisiologia, 2014)

(untitled)
OBJECTIVE: Duchenne muscular dystrophy (DMD) is the most common form of muscular dystrophy in children, and children with DMD die prematurely because of respiratory failure. We sought to determine the efficacy and safety of yoga breathing exercises, as well as the effects of those exercises on respiratory function, in such children. METHODS: This was a prospective open-label study of patients with a confirmed diagnosis of DMD, recruited from among those followed at the neurology outpatient clinic of a university hospital in the city of São Paulo, Brazil. Participants were taught how to perform hatha yoga breathing exercises and were instructed to perform the exercises three times a day for 10 months. RESULTS: Of the 76 patients who entered the study, 35 dropped out and 15 were unable to perform the breathing exercises, 26 having therefore completed the study (mean age, 9.5 ± 2.3 years; body mass index, 18.2 ± 3.8 kg/m(2)). The yoga breathing exercises resulted in a significant increase in FVC (% of predicted: 82.3 ± 18.6% at baseline vs. 90.3 ± 22.5% at 10 months later; p = 0.02) and FEV(1) (% of predicted: 83.8 ± 16.6% at baseline vs. 90.1 ± 17.4% at 10 months later; p = 0.04). CONCLUSIONS: Yoga breathing exercises can improve pulmonary function in patients with DMD.